Impact of the Pre-a Motif on Truncated Hemoglobin N Activity - (:unkn) unknown (My University, 2023)
Tuberculosis (TB) remains the leading cause of death by an infectious agent and therefore a global health crisis, according to the most recent report by the World Health Organization. This is due, in part, to Mycobacterium tuberculosis’ impressive defensive mechanisms against immune response, as well as the rise of Multi-Drug Resistant strains that have recently developed. Towards the turn of the century, a small heme protein called truncated hemoglobin N (trHbN) was discovered to protect the bacteria against reactive nitrogen species by converting nitric oxide (NO) to nitrate at rates far exceeding those of myoglobin and closer to those of the well-known NO dioxygenase flavohemoglobin. Ferrous oxygenated trHbN (oxy-trHbN) first converts NO to nitrate, which leaves the protein in a ferric state (met-trHbN). Met-trHbN is re-reduced to give a 5-coordinate ferrous species (red-trHbN), which is then re-oxygenated to oxy-trHbN. Recently, a unique 12-amino acid motif at the trHbN N-terminus was identified, the so-called pre-A tail, that appears to enhance the organism’s ability to convert NO to nitrate. The results presented herein show that the pre-A tail of trHbN affects every step of the putative NO dioxygenation catalytic cycle, but it affects the rate of met-trHbN re-reduction most profoundly. In a variant that lacks the pre-A tail (trHbNdelN), met-trHbNdelN was reduced about 40 times more slowly than met-trHbNWT by the non-specific reductant RuII. By comparison, the reactions of oxy-trHbN or red-trHbN with NO were only 2x – 4x slower in the trHbNdelN variant than in the wild type (the reaction of red-trHbN with NO is a good surrogate for the reaction of red-trHbN with O2). Importantly, the effect of the pre-A tail is completely lost in variants that lack distal site residues Tyr33 and Gln 58. These residues help to hold O2 firmly on the heme in oxy-trHbN, and a water molecule on the heme of met-trHbN. They also anchor a non-coordinated water molecule in the distal site of red-trHbN that blocks access by incoming diatomic gases. In a variant that lacks Tyr33 and Gln 58 (trHbNDM), met-trHbNDM is reduced 5x more rapidly by RuII than is met- trHbNWT because the distal site is now either vacant or occupied by weakly bound water, so rate-limiting water loss upon heme reduction is accelerated. A variant that lacks Tyr33, Gln 58, and the pre-A tail (met-trHbNTM), is reduced by RuII at the same rate as is met-trHbNDM, showing that tail loss does not affect the reduction rate if the distal site amino acids are absent. This is strong evidence that the pre-A tail’s primary function is to facilitate release of the distal water molecule from met-trHbN, a function that is less important in met-trHbNDM and met-trHbNTM than it is in trHbNWT.